Symptoms of endometriosis among indigenous African women (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2021)
Background: Endometriosis is a common gynecological disease that significantly impacts women's health. It presents with dyspareunia, dysmenorrhea, chronic pelvic pain, and infertility. Globally, the prevalence of endometriosis is estimated to be 10 , with comprehensive literature on its % clinical presentation in developed countries. However, only scant literature exists in Africa.Objective: To determine the symptoms of endometriosis in indigenous African women.Methods: This was a prospective analytical cross- selection study that enrolled indigenous African women undergoing laparoscopic surgery in two tertiary hospitals in Nairobi, Kenya. The study population included women aged 18-49 years scheduled for laparoscopic surgery. Data on patient history, clinical, laparoscopic, and histopathological findings were entered and analyzed using the IBM statistical package for social sciences (SPSS), version 22.0. The statistical significance was set at p